Fenotipe Pasteurella multocida Penyebab Bronchopneumonia Pada Babi Di Yogyakarta - Victor Lenda; Novianti Neliyani Toelle (FAKULTAS KEDOKTERAN HEWAN UNIVERSITAS NUSA CENDANA, 2019)
Pasteurella multocida is an important species that are suspected to cause bronchopneumonia in pigs. Prevalence of pneumonia pasteurellosis in slaughter house between 30-80%. The purpose of this study were determined the microorganisms that caused respiratory disorders (cough) or pneumonia in pigs in Yogyakarta area with morphological and biochemical tests. A number of 6 pigs were obtained from some pig farming in Yogyakarta with clinical symptoms of pneumonia were necropted, isolated and identified the cause of pneumonia, followed by histopathological examination of the isolates.The results showed that P. multocida is one of the main causes of bronchopneumonia in pigs in Yogyakarta with clinical symptoms of anorexia, dipsnoea, cough with serous to mucopurulent exudation. Pulmo showed grayish hepatization on dorsocranial, multifocal hemorrhagic and congestion. Histopathological changes found fibrinous bronchopneumonia and catharrhal bronchopneumonia.